Smart IOT Arowana aquarium / Muhammad Fikry Danial Mohamad Fadzwi ... [et al.] - Mohamad Fadzwi, Muhammad Fikry Danial; Mohamad, Luqman Hakim; Mohd Shafie, Nursyafikah; Radzali, Rosfariza; Abd Rahim, Alhan Farhanah (2020)
IoT system has been provided or used in many sectors that makes human able to do work although they are miles apart. IoT can also be applied to monitor the condition of aquarium for Arowana fish. There are a few factors that need to be taken seriously in keeping Arowana fish such as the pH level and the water temperature. In this project, the pH sensor and temperature sensor were used to detect its current condition. At unwanted condition which is related to the pH level and water temperature, dosing pump and heat pump will turn ON while LED will lights up at current condition. At this moment, users will receive notification through their smartphone (SMS and e-mail) when these conditions occur. The notifications show the current condition of water temperature, the pH level and the pump that turn ON at certain time. Tinkercad has been used to construct the circuit while Thingspeak being used to store data. IFTT being used to connect the device with smartphone to receive notification.